Metagenomic Analysis Exploring Taxonomic and Functional Diversity of Soil Microbial Communities in Sugarcane Fields Applied with Organic Fertilizer. (21st October 2020) - Li, Ruoyu; Pang, Ziqin; Zhou, Yongmei; Fallah, Nyumah; Hu, Chaohua; Lin, Wenxiong; Yuan, Zhaonian
Abstract : Organic fertilizers are critically important to soil fertility, microbial communities, and sustainable agricultural strategies. We compared the effect of two fertilizer groups (organic+chemical fertilizer: OM, chemical fertilizer: CK) on sugarcane growth, by observing the difference in microbial communities and functions, soil nutrient status, and agronomic characters of sugarcane. The results showed that the sugar content and yield of sugarcane increased significantly under organic fertilizer treatment. We believe that the increased soil nutrient status and soil microorganisms are the reasons for this phenomenon. In addition, redundancy analysis (RDA) shows that the soil nutrient condition has a major impact on the soil microbial community. In comparison with CK, the species richness of Acidobacteria, Proteobacteria, Chloroflexi, and Gemmatimonadetes as well as the functional abundance of nucleotide metabolism and energy metabolism increased significantly in the OM field. Moreover, compared with CK, genes related to the absorption and biosynthesis of sulfate were more prominent in OM. Therefore, consecutive organic fertilizer application could be an effective method in reference to sustainable production of sugarcane.